Features of psychological indexes in the sportsmen of weight sport at different weather terms. - Kulthickiy Z.I (Kharkov National Pedagogical University, 2011)
Psychological indexes are considered namely: the students of group of body-conditioning and sportsmen of weight sport have a will-power and perception of sentinel intervals. In research took part 20 students of group of body-conditioning, 16 sportsmen of weight sport of 3th digit and 16 sportsmen of 2th digit, men by the age 18-22 years. Researches conducted 1th and 3th type of weather. It is set that a will-power sportsmen of weight sport depends on a sporting digit and changes at the different types of weather. The change of weather influences on the processes of perception of time. At the 3th type of weather, in comparing to the 1th type, there is an acceleration of account of time in all inspected groups.